Surface and catalyst driven singlet oxygen formation in Li-O2 cells. (1st December 2020) - Samojlov, Aleksej; Schuster, David; Kahr, Jürgen; Freunberger, Stefan A.
Abstract: Large overpotentials upon discharge and charge of Li-O2 cells have motivated extensive research into heterogeneous solid electrocatalysts or non-carbon electrodes with the aim to improve rate capability, round-trip efficiency, and cycle life. These features are equally governed by parasitic reactions, which are now recognized to be caused by formation of the highly reactive singlet oxygen ( 1 O2 ). However, the link between the presence of electrocatalysts and 1 O2 formation in metal-O2 cells is unknown. Here, we show that, compared to pristine carbon black electrodes, a representative selection of electrocatalysts or non-carbon electrodes (noble metal, transition metal compounds) may both slightly reduce or severely increase the 1 O2 formation. The individual reaction steps, where the surfaces impact the 1 O2 yield are deciphered, showing that 1 O2 yields from superoxide disproportionation as well as the decomposition of traces of H2 O2 are sensitive to catalysts. Transition metal compounds in general are prone to increase 1 O2 . The results highlight the importance of 1 O2 in metal-O2 cells and to use a comprehensive set of metrics to judge the impact of catalysts on reversibility.